Implementation of a Combination of Insulin Therapy and Foot Exercises on Lowering Blood Glucose in Patients with Diabetes Mellitus - Wahyu Setiyawan; Nur Mutia Rosita; Purwanto Ika; Sopiah Yayah (AACENDIKIA: Journal of Nursing, 2026)
Diabetes mellitus is a chronic metabolic disorder characterized by persistent hyperglycemia resulting from inadequate insulin production or impaired insulin utilization. Blood glucose can be managed through pharmacological and non-pharmacological approaches. Combining insulin therapy with diabetic foot exercises may improve insulin sensitivity and peripheral blood circulation, thereby helping to reduce blood glucose levels. This study aimed to describe the implementation of combined insulin therapy and diabetic foot exercises in patients with diabetes mellitus at Dr. Adjidarmo General Hospital, Rangkasbitung. A case study design was conducted involving two patients with diabetes mellitus over a three-day observation period. Data were collected through interviews, physical examinations, observations, blood glucose measurements, and documentation. Following the combined intervention for 3 × 24 hours, both patients experienced reductions in blood glucose levels accompanied by improvements in hyperglycemic symptoms, including dizziness, weakness, excessive thirst, and polyuria. These findings suggest that combining insulin therapy with diabetic foot exercises may contribute to improved short-term glycemic control. Nurses play an essential role in providing health education, encouraging treatment adherence, promoting regular foot exercises, and supporting healthy lifestyle practices to maintain blood glucose control and prevent diabetes-related complications.